A standardized Boswellia serrata extract shows improvements in knee osteoarthritis within five days-a double-blind, randomized, three-arm, parallel-group, multi-center, placebo-controlled trial - Majeed, Anju; Majeed, Shaheen; Satish, G.; Manjunatha, R.; Rabbani, Shaikh Nawazish; Patil, Neelanagowda V. P.; Mundkur, Lakshmi (Frontiers in Pharmacology, 2024)
Background and objective: Boswellin ® Super is a standardized extract of Boswellia serrata gum resin, standardized to contain 30% 3-acetyl-11-keto-β-boswellic acid along with other β-boswellic acids (BSE). A randomized, double-blind, placebo-controlled clinical trial was conducted at two doses of BSE to understand its safety and efficacy in supporting joint health and improving mobility and symptoms of osteoarthritis (OA) of the knee.Methods: Based on the inclusion/exclusion criteria, 105 newly diagnosed participants with degenerative hypertrophy OA were recruited and randomized to receive to receive either 150 mg or 300 mg BSE or a placebo tablet twice a day for 90 days (n =35 in each group). All the participants were evaluated for pain and physical function using the Visual Analog Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Lequesne Functional Index (LFI), EuroQol-5 Dimension (EQ-5D) quality of life, six-minute walk test on days 0, 5, 30, 60 and 90.Additionally, the circulating levels of inflammatory biomarkers, tumor necrosis factor-α (TNFα), highsensitive C-reactive protein (hs-CRP), and interleukin-6 (IL-6) were evaluated. Safety was evaluated by monitoring adverse events throughout the study and blood biochemical, hematological, and urinary analyses.Results: Ninety-eight subjects completed the study. Improvements in pain scores were observed as early as five days in the BSE-150 and BSE-300 groups. By 90 days, the VAS pain score reduced by 45.3% and 61.9%, WOMAC-total score improved by 68.5% and 73.6% in the BSE-150 and BSE-300 groups respectively. WOMAC pain (70.2%, 73.9%, WOMAC stiffness (65.6%,68.9%), WOMAC function (68.8%,74.2%), LFI severity (50%,53.3%), decreased and EQ5D (56.9%, 62.9%) and distance walked in six minutes (21.2%, 21.9%) improved in the BSE-150 and BSE-300 groups in 90 days.Further, the levels of TNFα, hs-CRP, and IL-6 were found to decrease in the serum in BSEsupplemented participants. No significant adverse events were recorded during the study.The study confirms that Boswellin ® Super can be used as a safe and effective supplement to support joint health and mobility in the management of osteoarthritis.The trial was registered prospectively with the Clinical Trial Registry of India (CTRI) with the registration number CTRI/2022/11/047397